Adverse-drug reaction reporting by Pharm D students during hospital training - Anan S. Jarab; Walid Al-Qerem; Ghassan Shattat; Shrouq Abu Heshmeh; Tareq L. Mukattash; Salah Aburuz (Elsevier, 2023)
Background: Hospital pharmacists can play an important role in the detection, prevention, and reporting of adverse drug reaction (ADR) since they interact with patients in hospital settings. The ADR reporting practice by Pharm D students, who represent the future hospital pharmacists, has not been adequately investigated in the literature. Objective: To evaluate Pharm D students' knowledge, attitude, and practice regarding ADR reporting, and the associated barriers and motivators to ADR reporting during clinical training at different hospital sites in Jordan. Methods: The present cross-sectional study was conducted on sixth year pharm D students during clinical training at different hospital departments in different hospital sites Jordan. In addition to socio-demographic variables, a structured self-reported questionnaire was used to assess students' knowledge, attitude, practice, barriers, and motivators towards ADR reporting. Binary logistic regression was used to explore the variables associated with the study outcomes. Results: A total of 497 students participated in the study. The participants showed inadequate knowledge regarding ADR reporting, with a mean knowledge score of 3.20 (±1.78). On the other hand, the study participants showed positive attitude towards ADR reporting with a total mean score of 13.6 (±1.96). However, the ADR reporting practice was low with a mean score of 5.78 (±1.88). Not knowing how to report (60.2%) and not knowing where to report (55.9%) were the most common barriers to ADR reporting, while the most reported motivators for ADR reporting were seriousness of reaction (84.1%) and involvement of new drug (51.1%). Logistic regression analysis showed that time from the start of training (OR = 0.510; 95%CI = 0.305-0.852; P = 0.010), female gender (OR = 1.759; 95%CI = 1.083-2.857; P = 0.022), and attending a course/workshop about pharmacovigilance (OR = 0.213; 95%CI = 0.137-0.332; P = 0.00) were significant predictors of knowledge about ADR reporting. Increased age (OR = 0.93; 95%CI = 0.880-0.997; P = 0.041) and low knowledge (OR = 0.564; 95%CI = 0.380-0.837; P = 0.004) were significantly associated with negative attitude toward ADR reporting. Female gender (OR = 0.481; 95%CI = 0.302-0.766; P = 0.002) and attitude level (OR = 1.837; 95%CI = 1.205-2.802; P = 0.005) were significant predictors of ADR reporting practice. Conclusions: Pharm D students showed positive attitude towards ADR reporting, however, the knowledge and practice of ADR reporting were inadequate and the participants reported several barriers. Therefore, the topic of ADR reporting and pharmacovigilance, as well as, educational training programs need to be included in future pharmacy curriculum in order to improve students' awareness and practice of ADR reporting.